Knowledge and Practice of Postnatal Mothers Regarding Newborn Care at Hospital Settings - Sadique, Zahir; Sarker, Md Ferdousur Rahman; Yasmin, Sabina; Chowdhury, Jamal Pasha; Alam, Rumana (Journal of Armed Forces Medical College, Bangladesh, 2025)
Background: Although neonatal mortality rates have reduced in Bangladesh, still it’s prevalent in high number in the country. Neonatal mortality can be reduced by providing proper antenatal newborn care. Newborn care can be improved if parents are knowledgeable on different areas of newborn care. Objective: To evaluate the knowledge and practices of mothers on different areas of newborn care and factors that can influence the quality of newborn care. Methods: This cross-sectional study was conducted among 100 randomly selected mothers at the Combined Military Hospital Savar, Bangladesh between 01 October 2022 and 30 September 2023. A structured, self completed, closed ended questionnaire was delivered to 100 mothers who visited the Pediatric outpatient unit of the hospital with their neonates due to different clinical conditions. Results: Approximately 65% of mothers who filled out the form had good knowledge on neonatal care. Educational status of the mother, number of gravida and positive antenatal care visit were associated with better outcome. Mothers who had higher education and had opportunities to attend antepartum visit/visits were found to have good newborn care knowledge. Conclusion: More than half of the mothers who participated in the study had good knowledge regarding postnatal care for their babies. Gaps between the knowledge and practices were also noticed. Therefore, we recommend that stakeholders of the health sector have a close follow-up on maternal and newborn care services and maintain a strategy that will incorporate maternal education service in essential newborn care practice. JAFMC Bangladesh, Vol 20, No 2 (December) 2024: 11-15